EP1281 Total parietal peritonectomy: what morbidity? and which sites of recurrence? - Hudry, D; Berthet, A; Saadeh, R; Le Deley, MC; Narducci, F; Leblanc, E (International journal of gynecological cancer, 2019)
Introduction/BackgroundTo evaluate the morbidity of perioperative total parietal peritonectomy (TPP) during cytoreduction surgery (CRS), and its impact on the site of recurrence of different peritoneal surface malignancies (PSM).MethodologyWe led a retrospective study in a French tertiary cancer institution (Centre Oscar Lambret - Lille) experienced in treating PSM over a 6-year period from 2012 to 2018. All patients underwent a total parietal peritonectomy during a debulking surgery for PSM including ovarian cancer, appendiceal pseudomyxoma peritonei or peritoneal mesothelioma.ResultsSixty-one patients were included in this study with 79% of them having ovarian cancer. The rate of optimal surgery reached 87% with almost 70% of surgeries being highly complicated. 74.2% were transfused during the surgical procedure. The median hospitalization stay was 10 days including 7 days in Intensive Care Unit (ICU). 30% had early postoperative complications with no grade 4 and 42% Grade 3 complications. After a 30-months median follow-up, 84% of ovarian cancer group had no recurrence of the disease the first year and a 3-year survival of 77%. The main site of first and second recurrence was peritoneal (51% and 56.3%). In this series, there have been no cases of metastatic evolution of the abdominal wall.ConclusionTPP is a feasible surgical procedure to treat peritoneal surface malignancies and their recurrences with a low rate of Grade 3–4 morbidity. Even though, TPP doesn’t prevent peritoneal recurrence, it allow optimal surgery.DisclosureNothing to disclose